2013
DOI: 10.1371/journal.pone.0082944
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Targeting of the Orai1 Calcium Channel Inhibits T Cell Function

Abstract: Despite the attractiveness of ion channels as therapeutic targets, there are no examples of monoclonal antibodies directed against ion channels in clinical development. Antibody-mediated inhibition of ion channels could offer a directed, specific therapeutic approach. To investigate the potential of inhibiting ion channel function with an antibody, we focused on Orai1, the pore subunit of the calcium channel responsible for store-operated calcium entry (SOCE) in T cells. Effector T cells are key drivers of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…Two independently developed monoclonal antibodies selectively bound ORAI1 (but not ORAI2 and ORAI3), inhibited CRAC currents and SOCE in lymphocytes and suppressed the proliferation and cytokine production of human PBMCs and synovial fluid cells from rheumatoid arthritis patients in vitro (358, 359). In vivo treatment with anti-ORAI1 antibodies ameliorated the severity of xenogeneic T cell–mediated GvHD in mice (358) and reduced the production of IL-2, IL-4, and IL-17 by ex vivo–stimulated T cells isolated from cynomolgus monkeys (360). Collectively, these data suggest that CRAC channel inhibition may be useful for the treatment of autoimmune diseases, transplant rejection, and allergic diseases.…”
Section: Ion Channels As Drug Targets For Immunotherapymentioning
confidence: 99%
“…Two independently developed monoclonal antibodies selectively bound ORAI1 (but not ORAI2 and ORAI3), inhibited CRAC currents and SOCE in lymphocytes and suppressed the proliferation and cytokine production of human PBMCs and synovial fluid cells from rheumatoid arthritis patients in vitro (358, 359). In vivo treatment with anti-ORAI1 antibodies ameliorated the severity of xenogeneic T cell–mediated GvHD in mice (358) and reduced the production of IL-2, IL-4, and IL-17 by ex vivo–stimulated T cells isolated from cynomolgus monkeys (360). Collectively, these data suggest that CRAC channel inhibition may be useful for the treatment of autoimmune diseases, transplant rejection, and allergic diseases.…”
Section: Ion Channels As Drug Targets For Immunotherapymentioning
confidence: 99%
“…Taking a similar approach, another specific anti-Orai1 mAb targeting the second extracellular loop, inhibits the proliferation of T cells and cytokine production both in vitro and in vivo . Further mechanistic studies suggested that mAb-targeted Orai1 proteins are internalized, which resulting in loss of functional SOCE activity 211 . Although the anti-Orai1 mAbs-based potential therapy is limited in immune diseases, it raises high hope of similar application for cancer treatment.…”
Section: Drugs Targeting Ca2+ Channels/transporters/pumps For Cancermentioning
confidence: 99%
“…Due to the structural and functional diversity of ion channels, different strategies need to be considered for generation of antigen formats of the ion channel or antigens derived from the channel (Wilkinson, Gardener, & Williams, ). While peptides derived from the ion channel can be used as antigens (Cox et al., ), it is usual to use a conformationally relevant form of the channel as the antigen (Bednenko et al., ). Ion channels are normally expressed in low abundance in vivo and the heterologous expression of the proteins needed to achieve high expression levels requires considerable experimentation to optimize the host expression system, particularly as heterologous overexpression can be toxic (Vu, Bautos, Hong, & Gelli, ).…”
Section: Antibody Generation and Ion Channel Antigen Formatsmentioning
confidence: 99%